PENDAMPINGAN PEMUDA DESA SUMBEREJO DALAM PENGUATAN MENTAL SPIRITUAL MELALUI MAJELIS DZIKIR BASMALAH - Ainun Najib (LP2M Universitas Ibrahimy, 2021)
The role of pesantren colleges has a big responsibility in fostering and developing the potential of the surrounding community, especially for the younger generation who become assets to continue struggles in the future. The threat of drying up spiritual values ​​among the younger generation is getting away from behavior that is in accordance with the expected morality. So the youth mentoring program in strengthening mental-spirituality is one of the efforts to care for geranerasi through participatory transfromative social change actions. Preventive efforts to equip adolescents with religious knowledge and mental and spiritual strengthening, not only have a positive impact personally, but will also benefit the community around them. Together with stakeholders who have a significant role, this program emphasizes the assistance and empowerment of the community in understanding and resolving their own social problems, especially in the religious field. The continuity of the program which is carried out simultaneously will continue to be directed at developing the potential of future generations, while still integrating the roles and functions of the youth of the village of Sumberejo, which play an active role in spreading the da’wah of Islam rahmatan lil ‘alamin.